2011
DOI: 10.1155/2011/212737
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Adaptive and Real-Time Protocols Based on IEEE 802.15.4

Abstract: The IEEE 802.15.4 standard is a protocol that has been widely used in many applications exploiting wireless sensor networks (WSNs). However, it does not provide any means of differentiated services to improve the quality of service (QoS) for time-critical and delay-sensitive events. Furthermore, adaptive throughput performance for individual nodes cannot be supported with the current specifications. In this survey paper, we first discuss the negative aspects of IEEE 802.15.4 MAC in contention access period, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…It has been shown that tuning Reprinted from ref. [19] adequately the BE parameter of slotted CSMA/CA may result in an improved quality of service for time-critical messages.…”
Section: Adaptive Backoff Exponent Mechanismmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that tuning Reprinted from ref. [19] adequately the BE parameter of slotted CSMA/CA may result in an improved quality of service for time-critical messages.…”
Section: Adaptive Backoff Exponent Mechanismmentioning
confidence: 99%
“…Reprinted from ref. [19] networks. CWD is a mechanism assigning various values of CW according to the priority classes.…”
Section: Adaptive Contention Window Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the IEEE 802.15.4 [8] model is implemented in detail. Among others, both ZigBee and, to some extent, WirelessHART devices rely on the physical layer and data link layer specified in this standard [9], which makes it especially relevant for the CPS community. Contention-based (Carrier-Sense Multiple Access with Collision Avoidance) as well as contention-free (Guaranteed Time Slot, GTS) access mechanisms are implemented, as descibed in the standard.…”
Section: A Simulation Principlesmentioning
confidence: 99%